'Maledetta Signora' Storia dell'antijuventinismo (1897-2023) - Bellifemine, Onofrio (Strumenti per la didattica e la ricerca, 2023)
Juventus is a national symbol, the most loved club by Italian people, but also the most hated. The disdained, the hostility, the controversial that follows this team has no equal in the history of Italian sport. The anijuventinism is a cultural phenomena very complex that meets the history and the evolution of Italian football and also the whole country. All the controversy about the "Vecchia Signora" (the "Old Lady") are the football projection of strong and deep feelings as the rejection of authority, conspiracy, populism and suspect about the institutions. Thanks to a historical analysis, this book tries to tell about a popular history that goes beyond football.